MSME Accounting Revolution from Perceptions, Challenges, Solutions - Mochammad Fani Rafael; Sarwendah Biduri (Indonesian Journal of Law and Economics Review, 2024)
This study investigates the perceptions of Micro, Small, and Medium Enterprises (MSMEs) regarding accounting practices, focusing on Citra Pertiwi Farm and SUGOfreshmilk. Using a qualitative approach with interviews, observations, and documentation, the research identifies positive perceptions of accounting's benefits while noting shortcomings in inventory recording and accounts payable management. The study concludes that the current accounting practices in these MSMEs do not fully align with accounting standards for MSMEs. The findings suggest a need for improved accounting systems in MSMEs to enhance financial management and sustainability. Highlight: MSMEs' perceptions of accounting practices. Benefits and shortcomings in MSMEs' accounting. Emphasizes need for improved accounting systems. Keyword: MSMEs, Perception, Accounting, Improvement, Financial Management